(untitled) (Global Journal of Medical Research, 2022)
Aim of the study Over the last years the cognitive and mental health impairment in Multiple Sclerosis MS are indicated as important clinical symptoms in the course of the disease Every beneficial therapeutic management with this target could lessen the disability caused by the disease and improve the quality of life of MS patients It is known that Extra Virgin Olive Oil EVOO can exert positive effects on cognition regarding neurodegenerative diseases Phenolic compounds in EVOO have antioxidative and anti-inflammatory effects on the brain but all the mechanisms are not clear yet The present pilot study examines the benefits of early harvest EVOO EH EVOO on cognition and mental health regarding MS